Advanced oxidation processes for waste water treatment: from laboratory-scale model water to on-site real waste water. Issue 25 (10th November 2021) - Mahy, Julien G.; Wolfs, Cédric; Vreuls, Christelle; Drot, Stéphane; Dircks, Sophia; Boergers, Andrea; Tuerk, Jochen; Hermans, Sophie; Lambert, Stéphanie D.
ABSTRACT: A process combining three steps has been developed as a tertiary treatment for waste water in order to remove micropollutants not eliminated by a conventional waste water treatment plant (WWTP). These three processes are ozonation, photocatalysis and granulated activated carbon adsorption. This process has been developed through three scales: laboratory, pilot and pre-industrial scale. At each scale, its efficiency has been assessed on different waste waters: laboratory-made water, industrial waste water (one from a company cleaning textiles and another from a company preparing culture media, both being in continuous production mode) and municipal waste water. At laboratory scale, a TiO2 -based photocatalytic coating has been produced and the combination of ozonation-UVC photocatalytic treatment has been evaluated on the laboratory-made water containing 22 micropollutants. The results showed an efficient activity leading to complete or partial degradation of all compounds and an effective carbon for residual micropollutant adsorption was highlighted. Experiments at pilot scale (100 L of water treated at 500 L/h from a tank of 200 L) corroborated the results obtained at laboratory scale. Moreover, tests on municipal waste water showed a decrease in toxicity, measured on Daphnia Magma, and a decrease in micropollutant concentration after treatment. Finally, a pre-industrial container was built and evaluated as a tertiary treatment at the WWTP Duisburg-Vierlinden. It is shown that the main parameters for the efficiency of the process are the flow rate and the light intensity. The photocatalyst plays a role by degrading the more resistant micropollutants. Adsorption permits an overall elimination >95% of all molecules detected. GRAPHICAL ABSTRACT: UF0001